An Overview of Solid Organ Transplantation in Patients With Sickle Cell Disease. Issue 3 (10th October 2022) - Sharpe, Claire C.; Suddle, Abid; Stuart-Smith, Sara
Abstract : Sickle cell disease is a common genetic disorder affecting >300 000 people across the world. The vast majority of patients cared for in high-resource settings live well into adulthood, but many develop a high burden of disease complications. Good standard of care including disease-modifying agents and transfusion programs limits the number of patients who develop end-stage organ disease, but for those that do, the prognosis can be very poor. Solid organ transplantation is a well-established mode of treatment for patients with sickle cell disease and kidney or liver failure, but appropriate patient selection and perioperative management are important for achieving good outcomes. Hematopoietic stem cell transplantation and gene therapy may offer novel treatment options for adult patients with chronic organ damage in the future, but these are not yet widely available. For now, good, holistic care and early intervention of end-organ complications can minimize the number of patients requiring solid organ transplantation later in life.